Reactive Oxygen Species (ROS) in cancer and cancer stem cells - Hikmah, Febrial; Hardiany, Novi Silvia (Penerbit Universiti Kebangsaan Malaysia, 2021)
Reactive Oxygen Species (ROS) are aerobic metabolic byproducts, mainly produced by mitochondria. Most types of cancer contain high amounts of ROS. An increase in endogenous ROS triggers adaptive changes, induces oxidative stress and cytotoxic. Oxidative stress can lead to cancer. But on the other hand, the radiotherapy treatment method induces the formation of ROS in the process of cell death. Resistance therapy in cancer cells is associated with high antioxidant enzymes that neutralize ROS in cancer cells. In addition, therapeutic resistance and recurrence are also associated with the presence of cancer stem cells (CSCs). Several studies have shown that ROS levels are found to be low in CSCs. Low levels of ROS are likely to play a role in the survival of CSCs. Therefore, modulation of ROS levels in CSCs can be used as an alternative therapy.